TATA KELOLA KOLABORATIF MANAJEMEN TANGGAP DARURAT BENCANA PANDEMI COVID-19 DI KABUPATEN GUNUNGKIDUL (Collaborative Governance Covid-19 Pandemic Disaster Emergency Response Management In Gunungkidul Regency) - Evi Nilawati (Jurnal Ilmu Administrasi: Media Pengembangan Ilmu dan Praktek Administrasi, 2022)
This research is about collaborative governance of the Covid-19 pandemic emergency response management. The Covid-19 has a negative impact on society. Collaboration of stakeholders is important so that handling of the impact of Covid-19 is more effective. By the principles of collaborative governance that government, private, and community have responsibility for solving public problems. This study aims to find out how collaborative governance is for emergency response management for the Covid-19 in Gunungkidul Regency. The study used a qualitative descriptive approach. Informants are determined with purposive sampling, including elements of the local government, the private sector, and the community. Based on the results of the study, it can be concluded that during the Covid-19 pandemic disaster emergency response, collaborative governance was carried out by various stakeholders. This is shown by the realization of the principle of togetherness, shared motivation, and the capacity for joint action of the actors in various emergency response activities. The handling of Covid-19 has been carried out according to the new public management principle in the form of a partnership between the public and the private. Suggestions for further researchers are to examine the collaboration governance in the economic and social recovery after the pandemic.